2018
DOI: 10.15835/buasvmcn-fst:0025
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Alcohol Consumption Among Romanian University Students- Preliminary Research

Abstract: Young people’s consumption of alcohol is an ongoing problem. Many young adults binge-drink alcohol excessively, with serious negative consequences thereafter. This preliminary research assessed risk factors associated with alcohol consumption, drinking problems and related consequences among university students. The study was carried out on a total of 1056 students from UASVM Cluj-Napoca, Romania. University students claimed altered states of health after drinking episodes: vomiting, abdominal pain, headache, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Due to health and safety reasons, or to social regulations, the beer market is witnessing a significant rise in the consumption of NAB, especially because it lacks the disadvantages associated with high alcohol contents. Globally, alcohol consumption is the third major health-risk factor with harmful consequences and serious social implications [46,47]. Thus, when considering the potential health benefits of beer, careful consideration should be given to novel brewing techniques and yeasts that could help to moderate or minimize alcohol content whilst optimizing the flavor and potential health effects [10,48,49].…”
Section: Non-alcoholic Beers: Alcohol-free and Low-alcohol Beersmentioning
confidence: 99%
“…Due to health and safety reasons, or to social regulations, the beer market is witnessing a significant rise in the consumption of NAB, especially because it lacks the disadvantages associated with high alcohol contents. Globally, alcohol consumption is the third major health-risk factor with harmful consequences and serious social implications [46,47]. Thus, when considering the potential health benefits of beer, careful consideration should be given to novel brewing techniques and yeasts that could help to moderate or minimize alcohol content whilst optimizing the flavor and potential health effects [10,48,49].…”
Section: Non-alcoholic Beers: Alcohol-free and Low-alcohol Beersmentioning
confidence: 99%
“…The transition from adolescence to adulthood, living apart from parents, with less parental support can be a stressful time for students, often associated with an increase AC, up to dangerous levels [ 5 , 6 ]. Multiple studies have reported heavy AC among university students as an emerging issue, which is often associated with a significant risk of adverse psychological, social, and physical health consequences, including injuries, unplanned sex, academic failure, and alcohol related problems later in life [ 7 , 8 , 9 ]. Motives for alcohol use differ between genders, so the adverse outcomes [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that moderate consumption of beer has a significant impact on health, such as reducing the risk of cardiovascular disease, diabetes, osteoporosis, dementia, and lowering blood cholesterol levels (Salanţă et al, 2018). But the potential health benefits of moderate beer consumption are limited by the negative consequences of alcohol intake and energy content (de Gaetano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%